تعليم الصوتيات العربية وتعلمها بالحاسوب (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
تتلخصُ فكرةُ البحثِ في كيفيةِ استخدام إمكانات الحاسوب في تعلّم اللغة العربية وتعليمها، وأهم الطرق التعليمية، وأنواع البرامج الحاسوبية المُتبعة في ذلك، ثم يتعرض لأسباب تأخر وضع برامج حاسوبية لتعلم اللغة العربية، والصعوبات التي تعترض ذلك، ليتناول البحثُ فكرةَ برنامج الصوتيات العربية الحاسوبي، ومنهجه، وطريقة بنائه، فيعتمد برنامج الصوتيات العربية على الطريقة التحليلية التي تبدأ من الجملة البسيطة، فالمُفردة، فالمَقطع الصوتي، فالصوت اللغوي، مستخدماً أسلوب الاستثارة – الاستجابة، عن طريق استعمال الصور والأسئلة، ومن خلال تنمية مهارات الاستماع / الاستظهار، إذْ يهدف هذا البرنامج إلى إرشاد المتعلمين من غير العرب إلى مخارج الأصوات الصامتة دون صفاتها، مُستخدماً التجربة الذاتية المصحوبة بصرياً بالتمثيل التشريحي المُتحرك، كما يحوي هذا البرنامج عدداً كبيراً من الألفاظ ذات الدلالات الحسية، بهدف تعلم نطق الأصوات العربية داخل النسج الصوتية العربية، ثم تعلم معانيها عن طريق استخدام الصور، من حيثُ هي وسيلة تعليمية، بهدف الربط بين الأصوات والدلالة، ولذلك يُعدُّ البرنامج مُعجماً لُغوياً بصرياً صوتياً مُبسطاً، ليصل البحثُ إلى نتائج المقارنةِ بين منهجه وطريقة بنائه والطرق التعليمية المتبعة في تعلم اللغات الأجنبية وأنواع البرامج الحاسوبية التعليمية المعروفة. Computer assisted Arabic language learning and teaching is the controlling idea that will be developed in this research. It will attempt to explore the most important methods and computer programs used for this aim. Moreover, this research will try to highlight the reasons and difficulties which hinder deploying such programs to learn Arabic language. This will lead to the idea of computational Arabic phonetics and methods, and the way of structuring them. Thus, this program of Arabic phonetics will start with the simple sentence, the word, the syllable, and then the phoneme. To accomplish this, the stimulus and response method may be adopted by using pictures, questions, and developing the skills of listening and memorizing. So this program may guide the non-native speakers of Arabic to the places of silent sounds articulation relying on self-experience accompanied with visually animate anatomy. This program will also include a large number of spoken items which have tangible connotations hoping to learn the manner of articulating Arabic phonemes after we learn their meanings by using pictures as teaching aids to create a link between the phonemes and their meanings. In conclusion, this program may be regarded as a simple, linguistic visual and phonetic dictionary aspiring to show the comparative results between the method and the way of structuring it on the one hand and the teaching approaches adopted in language acquisition and the various, familiar computer teaching programs on the other hand.